A dynamic closed-looped and multidimensional model for Mental Workload evaluation. Issue 19 (2016) - Kostenko, A.; Rauffet, P.; Chauvin, C.; Coppin, G.
Abstract: The interest in mental workload (MWL) has strongly increased over the last 40 years in ergonomics and engineering studies. However, the subject is still very controversial and there is a debate on the dimensions to be considered for representing and estimating the workload. This paper reinvestigates the modeling of the mental workload concept, by combining the model of Hart and Staveland (1988), which considers this concept as a multidimensional construction, and the models of Sperandio (1971) and Leplat (2006), which focus on the regulation of the activity by the operator. This combination reveals new relationships between the different dimensions of MWL, and especially points out a means of measuring and understanding the effect of regulation on the workload. To validate this proposed approach to the modeling of MWL, an experiment is conducted on the dynamic activity of area monitoring based on the management of a swarm of drones.